SEROTONIN PROFILE OF KINTAMANI DOGS IN THE BEHAVIOR OF GUNA, JAYA, PAKSA, TEK, KYUL (LOCAL BELIEFS) OF THE BALINESE COMMUNITY - Siswanto, Siswanto; Dharmawan, Nyoman Sadra; Puja, I Ketut; Putra, I Gusti Agung Arta (Buletin Veteriner Udayana, 2023)
There is a belief in Bali which is the local wisdom of the Balinese people that the character of dogs is divided into guna, jaya, paksa, tek and kyul. Guna is a dog with an obedient character, useful and suitable as a hunting dog. Jaya is a dog with an attractive character, energetic, tends to be hyperactive. This type of dog is also good for hunting and paksa is a dog that is difficult to manage. This dog is suitable for house keeping. Tek is a dog with dirty behavior and is difficult to train or manage and kyul is a dog with a lazy character. The results showed that the character or nature of dogs is related to serotonin compounds in the blood. Aggressive dogs such as jaya and paksa have a low serotonin level profile. The purpose of this study was to determine the serotonin profile of different characters according to the beliefs of the Balinese people towards Kintamani dogs. A total of 30 Kintamani dogs were used as experimental animals. The research design used a cross-sectional study design. The results of the serotonin profile showed that the dogs with the characteristics of guna, jaya, paksa, tek and kyul were 114.4 ± 24.51; 98.5±28.47; 269.9±87.8; 316.6±54.8 and 256±15.1 (mmol/dl). It was concluded that the profile of the Kintamani dog according to the local belief of the Balinese people has normal serotonin levels.